2008
DOI: 10.1007/s10620-007-0139-0
|View full text |Cite
|
Sign up to set email alerts
|

The COX-2 Selective Inhibitor-Independent COX-2 Effect on Colon Carcinoma Cells is Associated with the Delta1/Notch1 Pathway

Abstract: Our results show that the selective COX-2 inhibitor may inhibit the proliferation and induce apoptosis in colon cancer cells through the COX-2-dependent pathway (HT-29) by decreasing the COX-2 mRNA/PGE2 levels and the activity of the COX-2-independent pathway (SW480). The Notch1 signal pathway mediates the effects of the COX-2 inhibitor on the proliferation and apoptosis of colon cancer cells. This may be a new target of the selective COX-2 inhibitor effect on colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…In our study, COX-2 protein expression paralleled the increase in VEGF protein in ES cells exposed to hypoxia and was associated with increased mouse ES cell proliferation. Furthermore, the increase of Notch-1 and cleaved Notch-1 was blocked by COX-2 inhibitor, which is consistent with previous results (42). Upon activation, Notch is cleaved, releasing intracellular Notch, which translocates into the nucleus where it associates with transcription factors, regulating the expression of target genes and thus playing an important role in development and cell growth (32,40).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, COX-2 protein expression paralleled the increase in VEGF protein in ES cells exposed to hypoxia and was associated with increased mouse ES cell proliferation. Furthermore, the increase of Notch-1 and cleaved Notch-1 was blocked by COX-2 inhibitor, which is consistent with previous results (42). Upon activation, Notch is cleaved, releasing intracellular Notch, which translocates into the nucleus where it associates with transcription factors, regulating the expression of target genes and thus playing an important role in development and cell growth (32,40).…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have identified a series of new molecular targets of NSAIDs that are mainly involved in signaling pathways, i.e. activation of MAPKs and AKT [12] inhibition of Delta/ Notch1 [43], etc, but in these cases the applied NSAID concentrations, which are required to influence these pathways were more than tenfold higher than those used in our investigations.…”
Section: Cox-2 Protein Expression Determined By Western Blotting and mentioning
confidence: 72%
“…Indeed, a substantial number of experimental data indicates that non-steroidal antiinflammatory drugs (NSAID) may inhibit colon cancer development. The anticancer activity of most of them is based on their selective inhibitory effect on cyclooxygenase-2 (COX-2) activities, that play a crucial role in colon cancer development and progress [42] . In that sense, aspirin has drawn particular attention since it expresses an inhibitory activity on both COX-1 and COX-2 enzymes.…”
Section: Aspirinmentioning
confidence: 99%
“…In that sense, aspirin has drawn particular attention since it expresses an inhibitory activity on both COX-1 and COX-2 enzymes. However, studies have showed that NSAID anti-cancer properties may proceed also through COX-independent pathways, such as inappropriately Delta1/Notch1 signal transduction pathway, and upregulation of NAG-1 gene that is a member of the TGF-β superfamily [42][43][44] . Bergman et al [45] have found that addition of aspirin to PBMC and adaptive immunity is gaining importance.…”
Section: Aspirinmentioning
confidence: 99%